The Value of Citizen Science in Increasing Our Knowledge of Under-Sampled Biodiversity: An Overview of Public Documentation of Auchenorrhyncha and the Hoppers of North Carolina - Kittelberger, Kyle D.; Hendrix, Solomon V.; Şekercioğlu, Çağan Hakkı (Frontiers in Environmental Science, 2021)
Due to the increasing popularity of websites specializing in nature documentation, there has been a surge in the number of people enthusiastic about observing and documenting nature over the past two decades. These citizen scientists are recording biodiversity on unprecedented temporal and spatial scales, rendering data of tremendous value to the scientific community. In this study, we investigate the role of citizen science in increasing knowledge of global biodiversity through the examination of notable contributions to the understanding of the insect suborder Auchenorrhyncha, also known as true hoppers, in North America. We have compiled a comprehensive summary of citizen science contributions, published and unpublished, to the understanding of hopper diversity, finding over fifty previously unpublished country and state records as well as dozens of undescribed and potentially undescribed species. We compare citizen science contributions to those published in the literature as well as specimen records in collections in the United States and Canada, illuminating the fact that the copious data afforded by citizen science contributions are underutilized. We also introduce the website Hoppers of North Carolina, a revolutionary new benchmark for tracking hopper diversity, disseminating knowledge from the literature, and incorporating citizen science. Finally, we provide a series of recommendations for both the entomological community and citizen science platforms on how best to approach, utilize, and increase the quality of sightings from the general public.